Nonlinear pharmacokinetics of rituximab in non‐Hodgkin lymphomas: A pilot study. Issue 9 (26th June 2019) - Ternant, David; Monjanel, Hélène; Venel, Yann; Prunier‐Aesch, Caroline; Arbion, Flavie; Colombat, Philippe; Paintaud, Gilles; Gyan, Emmanuel
Abstract : Aims: Rituximab is an anti‐CD20 monoclonal antibody approved in non‐Hodgkin lymphoma (NHL). This study aimed to assess the relationship between antigen mass and nonlinear pharmacokinetics of rituximab in NHL patients. Methods: In a retrospective cohort of 25 NHL patients treated with rituximab, antigen mass was assessed at baseline by measuring metabolic tumour volume (MTV) by positron emission tomography. Rituximab pharmacokinetics was described using a semimechanistic 2‐compartment model including a latent target antigen. Rituximab target‐mediated elimination was described as irreversible binding between rituximab and it target. Histology (follicular or diffuse large B‐cell lymphomas), initial MTV and body weight were tested as covariates on pharmacokinetic parameters. Results: The model allowed a satisfactory description of rituximab serum concentrations. Target‐mediated elimination was maximum at the beginning of treatment and became negligible towards the end of follow‐up. The second‐order elimination of rituximab due to target binding and complex elimination increased with baseline MTV. Central volume of distribution increased with body weight ( P = .022) and baseline MTV ( P = .005). Conclusions: This study quantified for the first time the target‐mediated elimination of rituximab in NHL patients and confirmed rituximab retention by antigen mass.